The refugee waves and the continuum of violence experienced by Ukrainian refugee women in Bulgaria - Pamporov, Alexey (Frontiers in Sociology, 2025)
This article examines the continuum of violence experienced by Ukrainian refugee women in Bulgaria over the past 3 years, following the full-scale invasion by the Russian army. The study draws on a secondary analysis and triangulation of three quantitative surveys commissioned by UNHCR and UNICEF in Bulgaria, along with three waves of a randomized socio-economic survey funded by UNHCR. Employing a constructivist grounded theory approach, the article proposes a typology of several refugee waves. It argues that the period of arrival, the means of arrival, and the type of accommodation selected reflect the survival strategies of refugee women and may influence their exposure to both community-based and transnational gender-based violence (GBV). The findings indicate that certain institutional features of Bulgaria’s state accommodation programme for individuals with temporary protection status expose women and girls to additional risks of GBV, including survival sex and relocation to areas associated with commercial sex work. The vulnerability of Ukrainian refugees is further exacerbated by three country-specific factors: institutional neglect of violence against women and girls; widespread acceptance of cultural myths related to sexual violence; and prevailing national stereotypes targeting Ukrainians and, more broadly, women from certain Slavic backgrounds. The analysis clarifies the various forms of the continuum of violence affecting the Ukrainian women and girls in Bulgaria and confirms the patterns of “slow violence” and the “violence of uncertainty,” observed in the Eastern Mediterranean region by other international studies.